2008
DOI: 10.1093/jac/dkn331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of integrons and associated resistance genes in faecal Escherichia coli isolates of healthy humans in Spain

Abstract: A high prevalence of integrons was detected in faecal E. coli of healthy humans. Individuals in the community could be a reservoir of integron-containing E. coli isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
57
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 8 publications
14
57
4
2
Order By: Relevance
“…The association of both classes of integrons with aadA genes has been demonstrated in numerous studies, for instance, as a part of the Tn7-like class 2 integron gene array dfrA1-sat1-aadA1 (30,51,52). The aadB marker, encoding resistance to gentamicin, kanamycin, and tobramycin, was identified in a single isolate as part of a 2.7-kb variable region within a class 1 integron along with aadA1 (1%) in a previously reported gene arrangement, aadB-aadA1 (30,52).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The association of both classes of integrons with aadA genes has been demonstrated in numerous studies, for instance, as a part of the Tn7-like class 2 integron gene array dfrA1-sat1-aadA1 (30,51,52). The aadB marker, encoding resistance to gentamicin, kanamycin, and tobramycin, was identified in a single isolate as part of a 2.7-kb variable region within a class 1 integron along with aadA1 (1%) in a previously reported gene arrangement, aadB-aadA1 (30,52).…”
Section: Discussionmentioning
confidence: 95%
“…Their extensive dissemination could be attributed to their association with integrons and plasmids (13,31,30,51).…”
Section: Discussionmentioning
confidence: 99%
“…dfrA17-aadA5 was the only gene cassette isolated from healthy farm workers in China (Li et al, 2010). Studies of commensal species isolated from healthy humans in Switzerland and Spain detected this same allele, although they reported the dfrA1-aadA1 arrangement to have a higher frequency (Cocchi et al, 2007;Vinué et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, 3 out of 100 (3.0%) E.coli strains revealed the presence of class 2 integron (Vinue et al, 2008). Su et al reported 4 out of 111 (3.6%) E. coli strains harboring class 2 integron with a classic cassette array dfrA1-sat1-aadA1.…”
Section: Class 2 Integronmentioning
confidence: 99%